Sanggar, pelimbonen, kaphaygo sa ragat: Traversing the Pre-Islamic beliefs and traditions of the Meranaws in the Philippines - Alican Mendez Pandapatan; Jamima Sandab Ampuan (SIMULACRA: JURNAL SOSIOLOGI, 2023)
The pre-Islamic culture in the Philippines is evident in the present social behavior of the Filipinos, especially the Meranaws. These people geographically occupy the two Lanao provinces and other nearby towns. This paper explored the tradition of sanggar, pelimbonen and kaphaygo sa ragat as ancient practices before the influence of Islam to the Meranaws. The practices involve the invocation of spirits, use of nature such as sea, plants, and spells. The study is a qualitative and the method used is descriptive analysis to explain and discuss the beliefs and traditions. The data were collected through interviews on the three concepts mentioned. The traditions and beliefs were rich embedded culture and widely practiced years before the Islamization of the Meranaws. They called spirits in nature as they believed in the power of these beings in treating people and the success of their spells. However, it is noted with the case of sea bathing, the Meranaws live near the lake, which calls for further investigation if this tradition is true for all Meranaws. No single document has ever proven this. Thus, some traditions and beliefs have been banned due to the influence of strong Islamic teachings.